Kaposi's varicelliform eruption in a patient with metastatic melanoma and primary cutaneous anaplastic large cell lymphoma treated with talimogene laherparepvec and nivolumab. Issue 1 (19th November 2018) - Miller, David M.; Trowbridge, Ryan M.; Desai, Anupam; Drews, Reed E.
Abstract : Background: Immune-directed therapies have become front-line therapy for melanoma and are transforming the management of advanced disease. In refractory cases, multi-modal immunoncology (IO) approaches are being utilized, including combining immune checkpoint blockade (ICB) with oncolytic herpes viruses. Talimogene laherparepvec (T-VEC) is the first genetically modified oncolytic viral therapy (OVT) approved for the treatment of recurrent and unresectable melanoma. The use of IO in patients with concomitant malignancies and/or compromised immune systems is limited due to systematic exclusion from clinical trials. For example, a single case report of a solid organ transplant patient successfully treated with T-VEC for metastatic melanoma has been reported. Furthermore, the use of ICB in T-cell malignancies is limited and paradoxical worsening has been described. To our knowledge, this is the first report of dual ICB/T-VEC being administered to a patient with concurrent primary cutaneous anaplastic large cell lymphoma (pcALCL) and melanoma. Case presentation: Here we present the case of a patient with concomitant primary cutaneous ALCL and metastatic melanoma, progressing on anti-programmed death (PD)-1 therapy, who developed Kaposi's varicelliform eruption after receiving the first dose of Talimogene laherparepvec. Conclusion: This case highlights the complexities of care of patients with coexistent cancers, demonstrates rapid progression of primary cutaneous ALCL on nivolumab and introduces a novel adverse effect of Talimogene laherparepvec.